Transcendental Epistemology Study of Philosophy of Wisdom Muta'aliyah Mulla Sadra - Fauziah Nurdin; Hasymsyah Nasution; Hasan Bakti Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The aim of the study is to find out Transcendental Epistemology by using Muta'aliyah Mulla Sadra. This study used qualitative research methodology. The result of the study is Mullâ Shadrâ system is different from the emphasis on specific aspects of "rationality" as it is now does not mean that its founder understands it as "irrational" nor is it given to "mystical experience". But the system emphasizes a world view that intuitive vision is an inseparable part of knowledge. With this method, knowledge or wisdom is obtained not only that is generated by the power of reason but also through spiritual enlightenment, and all of that is then presented in rational form using rational arguments. For Mullâ Shadrâ, knowledge or wisdom is not only to enlighten cognition but also realization; change the form of the recipient of enlightenment itself and realize the knowledge gained so that the transformation of form occurs. All that cannot be achieved except by following the Shari'a, so a thought must hook the infant method in its system.